Pengembangan E-Book Berbasis Pinterest “Pena Muhammad (Petualangan Nabi Muhammad)” Tentang Politik Rasulullah dalam Membangun Kota Madinah - Aeni, Ani Nur; Agustin, Dini; Putri, Mira Heryana; Ruhiyat, Ruhiyat (AS-SABIQUN, 2024)
This study aims to produce an innovative and effective approach to learning Islamic Religion (PAI) at the elementary level through the use of a Pinterest-based e-book entitled "PENA Muhammad (The Adventure of the Prophet Muhammad)". This research was conducted at SDN Cisempak, Wargaluyu Village, Tanjungmedar District, Sumedang Regency. This research uses a type of Design and Development (D&D) research with descriptive methods. Data were collected through direct observation and instrument validation. Researchers utilized Canva, Pinterest, Wordwall, Heyzine Flipbook, YouTube, and QR code generator applications and sites. The evaluation results showed a positive response from students to the "PENA Muhammad" e-book. Most students felt happy and successfully understood the material delivered through the e-book and demonstrated its effectiveness in improving their understanding of Islamic religious and political values, as well as its relevance in the context of modern life. The development of this e-book can be an effective innovation in learning PAI at the elementary level. By using an innovative approach through the Pinterest-based "PENA Muhammad" e-book, PAI learning for grade 3 elementary school students becomes more interesting and interactive. the development of this e-book can help students understand the Prophet's political material in building the City of Medina better. The use of multimedia and digital technology in learning provides an enjoyable and in-depth learning experience for students, so that they are able to understand the material better.